FAKTOR – FAKTOR YANG MEMENGARUHI PROFITABILITAS PADA PERUSAHAAN SEKTOR INDUSTRI DI INDONESIA - Yapriansen, Jonathan Natanael; Susanto, Liana (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study purpose is to see empirical evidence about factor that affect profitability in industrial sector companies listedion the Indonesia Stock Exchange for 2019-2021. Sample is selected with purposive sampling method and the sampel is 36 companies. The data management used multiple linear regression analysis operated with the SPSS (Statistical Producti and Service Solution) program version 25 and Microsoft Excel 2016. The results of the analysis in this study have indicator that leverage has a significant negative on profitability, while liquidity and company size have no significant effect on profitability. This research has implications, namely that companies are expected to increase their profitability by paying attention to factors that can affect profitability so that investors can trust in investing.